Two-exponential estimators for estimating population mean - Jabeen, Riffat; Sanaullah, Aamir; Hanif, Muhammad; Zaka, Azam (AIMS mathematics, 2021)
We introduce two-exponential shrinkage estimator using two stage two phase sampling for estimating population mean of study variable. Some properties of the proposed two-exponential shrinkage estimator are presented. The mathematical comparison in terms of the mean square error is done in order to demonstrate some conditions for which the proposed shrinkage estimators is more efficient than the already existing estimators in literature. A real life application is provided to show the performance of the proposed shrinkage estimator.